Zachowania zaradcze w średniej i później dorosłości = Coping behavior in middle and late adulthood - Kornienko, Innokentii, A. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The results of a comparative study of coping behavior of respondents in the period of middle and late adulthood are reviewed in the article. Different questionnaires based on various theoretical concepts of coping behavior were used. Statistical analysis to determine the significance of differences using the Mann-Whitney test was performed. Peculiarities of coping behavior of each analyzed age group, as well as the dominant behavioral coping strategies in early and late adulthood are determined. Stressors that produce the greatest impact on the personality in the middle and late adulthood are reviewed. The hypothesis that a person in middle age is at the peak of constructive coping repertoire is introduced. The problem of analysis of the role of aging in changing of the coping behavior of the personality with the absence of diseases, leading to physiological changes is updated.
Keywords: zachowania zaradcze; strategie radzenia sobie ze stresem (coping); stres; dorosłość; coping behavior; coping; adulthood